Structural Modification For High Rise Building For Energy Efficiency : A Review - AAvez; Prasad, Bikram (International Journal of Scientific Research in Civil Engineering, 2020)
Energy conservation in the built environment has become one of the most important topics on both political and scientific agendas. The rising global population, decreasing fossil-based energy resources, rising emissions of harmful gases have emerged as the main motivators for energy efficiency in buildings. In addition, cost efficiency, safety and the need to reduce carbon emissions are fundamental reasons for energy conservation. In the last century, the incredible increase in the amount of energy usage and the increasing dependence on energy resources have forced human beings to consume energy in the most efficient way in every area. The world is dominated by buildings with about 40% energy consumption. For this reason, the construction sector is affected by global energy issues, and the traces of these effects are manifested in the design, construction and usage processes of the buildings. In this context, energy efficient design systems related to the production of the buildings that draw so much of the world's energy consumption have been put forward. This Study scrutinizes approaches to energy efficiency in the buildings of the last century. In this paper we are presenting literature survey related to past researches related to designing and analysis of green buildings.
Keywords: Structural Analysis; Analysis Tool; Review; Tall Structures; Forces; Displacement